Patient Satisfaction Based on IOL Implantation Results - M. E. Konovalov; K. V. Burdel; M. L. Zenina; A. B. Reznikova; M. M. Konovalova (Oftalʹmologiâ)
Purpose: to found the relationship between the obtained postoperative visual acuity, the increase in visual acuity in the lines and the subjective satisfaction of patients with the results of the operation.Material and methods. The study included 165 patients (186 eyes) who received cataract phacoemulsification surgery with IOL implantation (n = 170) or refractive lensectomy with IOL implantation (n = 16). The average age of the subjects was 70.23 ± 10.14 years. The group included patients without concomitant systemic or ophthalmic pathology, without previous surgical interventions in the eye for any purpose. At least 1 month after the operation, patients filled out a questionnaire in order to find out the subjective satisfaction with the treatment (scale from 0 to 4 points). The results of the questionnaire were compared with postoperative BCVA, and increased vision (postoperative BCVA — preoperative BCVA). Preoperative BCVA — Me 0.4 (Q1–Q3: 0.1–0.68), postoperative BCVA — Me 1.0 (Q1–Q3: 0.95–1.0), increased vision — Me 0.6 (Q1–Q3: 0.3–0.9) according to Snellen’s table.Results. Visual acuity in satisfaction subgroups: 0 points — Me 1.0 (Q1–Q3: 0.9–1.0) / n = 5 (2.7 %); 1 point — 1 case, postoperative BCVA 1.16 (0.5 %); 2 points — Me 0.95 (Q1–Q3: 0.84–1.0) / n = 14 (7.5 %); 3 points — Me 1.0 (Q1–Q3: 0.9–1.16) / n = 57 (30.6 %); 4 points — Me 1.0 (Q1–Q3: 0.96–1.0) / n = 109 (58.6 %). Postoperative BCVA and increased in visual acuity do not have statistically significant differences depending on satisfaction with treatment (p > 0.05). The correlation between postoperative BCVA and satisfaction is not statistically significant (p = 0.65; rxy = 0.136), as well as between vision improvement and satisfaction (p = 0.55; rxy = 0.141).Conclusion. There was a lack of a statistically significant relationship between postoperative BCVA and improved vision with subjective patient satisfaction with treatment. Identification of factors affecting subjective assessment requires a deeper analysis. Practicing ophthalmologists should remember the importance of the dialogue between the doctor and the patient at the preoperative stage, informing the patient about the expected results of the operation and the possible course after the operation period.